Attack on Titan. 14 - Isayama, Hajime, 1986- (Kodansha Comics, 2014)
"Commander Erwin has finally come to a decision: Putting their own wealth and position ahead of the survival of humanity, the royal government is no longer fit to lead. To execute their leader's most audacious plan yet, Eren and Krista will have to put themselves in peril yet again, and Armin, Mikasa, and the rest of the Survey Corps will have to turn from humanity's guardians into traitors. If they fail this time, they'll face not a Titan's gaping mouth, but the gallows..."--P. [4] of cover.